Clinical features and long exercise test in Chinese patients with Andersen‐Tawil syndrome. Issue 6 (11th October 2016) - Song, Jie; Luo, Sushan; Cheng, Xin; Yue, Dongyue; Zhu, Wenhua; Lin, Jie; Huang, Jun; Lu, Jiahong; Zhao, Chongbo; Qiao, Kai
ABSTRACT: Introduction : Andersen‐Tawil syndrome (ATS) is a rare multisystem channelopathy characterized by periodic paralysis, ventricular arrhythmias, and developmental dysmorphology. There are few reports concerning ATS in the Chinese population. We analyzed clinical features and evaluated the long exercise test as a tool for diagnosis of periodic paralysis in ATS. Methods : Direct sequencing of KCNJ2 was performed in 12 subjects from mainland China with suspected ATS. Clinical features, therapeutic responses, and long exercise tests (LET) were retrospectively analyzed. Results : Twelve patients were genetically confirmed to have ATS. A small mandible and clinodactyly were demonstrated in all patients. Premature ventricular contractions were the most prevalent form of cardiac arrhythmia. The LET revealed an early amplitude decrement. Conclusions : Chinese ATS patients shared some common clinical features with reported subjects in other countries. An early amplitude decrement in LET may be useful for diagnosis of ATS. Muscle Nerve 54 : 1059–1063, 2016